The effectiveness of school anti-cyberbullying policies and their compliance with South African laws - Ganca, Simo-Sihle (Department of Information Systems, 2024)
With technological advances and an increased reliance on technology for schooling and other daily activities such as communication, students need to navigate the downside of the digital age; namely, cyberbullying. Cyberbullying continues to be a concern for parents, teachers, and the government as the number of students with access to technology increases. The fourth Social Development Goal (SDG 4) of the United Nations is focused on quality education. Cyberbullying has been associated with truancy which leads to students dropping out, poor academic performance and health issues such as depression and even suicide. These effects are contrary to the goal and left unchecked will impede the UNs 2030 target date, therefore, it is imperative to reduce cyberbullying. In this digital age it is becoming increasingly complex to regulate cyberbullying and protect the vulnerable such as students. Due to this problem, schools have been mandated to ensure the constitutional rights of their students to safety and education are not disrupted by cyberbullying. To comply, schools have developed policies, standards and frameworks that ensure these rights are met. Some schools developed and adopted a Code of Conduct, others specific anti-bullying and anti-cyberbullying policies, while some rely on a combination of policies including the Acceptable Use of Technology policies to meet their obligation of curbing cyberbullying. Current practices in developing these policies have however been deemed weak and the teachers developing them identified as ill-equipped. Little is known regarding the state of South African high schools' policies with no preceding research focusing on this in an African context. The purpose of this study is to determine the effectiveness of school cyberbullying policies by measuring whether these policies are in line with national regulations. To achieve this, the researcher using systematic literature review, synthesised existing literature identifying various theoretical works including the socio-ecological system theory which are used to support the developed conceptual framework. The literature review showed that for anticyberbullying policies to be effective and compliant, multiple conditions ought to be met. These key components include the Policy Content, Policy Development, Communication to students and parents and lastly regular Policy Reviews. If the above-mentioned conditions are not met by school policies, the policies adopted to address cyberbullying in schools are ineffective in reducing the extent of cyberbullying and therefore contravene the law. The hypotheses were tested using quantitative methods on data collected in Gauteng and the Western Cape. Two surveys were used to collect the results, the first to collect responses from school management on their perspectives on cyberbullying and cyberbullying policies in their schools, the other used to determine whether these policies contain the key components. In total 101 and 31 responses were collected respectively. Using Statistica, various tests were conducted including correlation analysis, frequencies and more. The findings from this research vary and bridge the gap in existing research where little is known about the effectiveness of policies adopted by to mitigate the increasing problem of cyberbullying. While studies of this nature have been carried around the globe, to the best of the researcher's knowledge, the work presented in this dissertation has not been tested in South Africa before. By focussing on South African high schools, this research contributes to literature by providing insight into whether policies used in schools are effective and robust. The finding of this study highlight the dire need for schools to be supported in developing the policies to address cyberbullying. Several interesting results were found during this study and will be discussed in chapter 4. Differing from other studies, this research does not support the notion of having stakeholders across the social ecology of students lives involved in the development of policies leads to effective policies; this could be due to the stakeholders not being qualified through training prior. This would need to be investigated by future research Keywords: Cyberbullying, Anti-cyberbullying, School anti-cyberbullying policy, Students